Riga-Fede disease: a mimicker of malignancy - Lakshmanan, Somu (BMJ Case Rep, 2021)
Riga-Fede disease (RFD), also known as traumatic eosinophilic granuloma, is a benign inflammatory condition of the oral cavity that may mimic a malignant tumour. It’s a rare condition mainly reported in infants. We present a unique case report of a 57-year-old man who presented to our outpatient department with foreign body sensation in the throat and swelling over the dorsum of the tongue for a period of 1 month. He gave no history of trauma, especially due to sharp teeth. Video laryngoscopy done revealed an ulceroproliferative growth on the midline of the dorsum of the tongue. With clinical suspicion of malignancy, the patient underwent wide local excision of the tongue lesion. Histopathological examination was suggestive of RFD. The postoperative follow-up was uneventful with good wound healing. The patient was followed up with no evidence of recurrence.